Safety sign comprehension by adult workers to measure worker safety: A literature review - Qurratul A'yun Az-Zahra; Hanifa Maher Denny; Yuliani Setyaningsih (Holistik Jurnal Kesehatan, 2024)
Background: Work-related accidents are a problem throughout the world. In the United States, work-related accidents reached 2.3 million workers who underwent treatment in emergency units in 2019. The K3 promotion program in the workplace was designed as an effort to increase workers' self-efficacy for risks that occur in the workplace. One type of occupational safety and health promotion in the workplace is safety signs. Purpose: To provide information to workers regarding danger warnings in the work environment Method: This research uses literature review techniques and obtains search data from Elsevier and Google Scholar using the keywords employee and safety sign, work accident. The inclusion criteria for the literature review are articles published within the last 5 years, namely 2019-2023, journals published on the theme of safety signs in the workplace, open access journals, and full text. Results: Implementation of safety signs that comply with standards in the workplace to notify workers of danger signs is very important. This is to get personal protection and to save yourself if a disaster or work accident occurs. Conclusion: Changes to danger area signs in port terminals are needed to improve work safety and reduce accidents. Proper installation of safety signs in the workplace can influence the behavior of workers, and refugees, and improve overall workplace safety. Apart from that, workers' compliance and knowledge of work safety rules also plays an important role in improving workplace safety.   Keywords: Safety; Safety Sign; Worker.   Pendahuluan: Kecelakaan akibat kerja merupakan masalah di seluruh dunia. Di Amerika Serikat kecelakaan akibat pekerjaan mencapai 2.3 juta pekerja yang menjalani perawatan di unit gawat darurat pada tahun 2019. Program promosi K3 di tempat kerja, disusun sebagai upaya meningkatkan kemampuan diri pekerja terhadap risiko-risiko yang terjadi di tempat kerja. Salah satu jenis promosi keselamatan dan kesehatan kerja yang ada di tempat kerja yaitu safety sign. Tujuan: Untuk memberikan informasi kepada pekerja terkait peringatan bahaya yang ada di lingkungan kerja Metode:  Penelitian ini menggunakan teknik literature review dan mendapatkan data search dari Elsevier dan Google scholar dengan menggunakan kata kunci employee and safety sign, work accident. Kriteria inklusi pada literature review yaitu artikel yang diterbitkan dalam waktu 5 tahun terakhir yaitu 2019-2023, jurnal hasil publikasi yang memiliki tema safety sign di tempat kerja, open access journal, dan full text. Hasil: Penerapan safety sign yang sesuai dengan standar di tempat kerja untuk memberitahu pekerja tentang tanda-tanda bahaya sangat penting. Hal ini agar mendapatkan perlindungan pribadi dan untuk menyelamatkan diri apabila sewaktu waktu terjadinya bencana atau kecelakaan kerja. Simpulan: Perubahan pada tanda area bahaya di terminal pelabuhan diperlukan untuk meningkatkan keselamatan kerja dan mengurangi kecelakaan. Pemasangan rambu keselamatan yang tepat di tempat kerja dapat mempengaruhi perilaku pekerja, dan pengungsi, serta meningkatkan keselamatan kerja secara keseluruhan. Selain itu, kepatuhan dan pengetahuan pekerja tentang aturan keselamatan kerja juga berperan penting dalam meningkatkan keselamatan di tempat kerja.   Kata Kunci: Keselamatan; Pekerja; Tanda Keselamatan.